Assessment of food consumption and socioeconomic conditions of patients undergoing hemodialysis therapy in the interior of Paraíba (Research, Society and Development, 2020)
The hemodialysis patient undergoes numerous changes in diet. Food has an influence on the prognosis of renal patients undergoing hemodialysis and socioeconomic factors can determine food choice and adherence to treatment. From then on, the objective was to evaluate the socioeconomic conditions and food consumption of patients on chronic hemodialysis in the city of Patos, Paraíba. This is a cross-sectional study, with a quantitative approach, carried out with 29 adult patients, with chronic kidney disease undergoing hemodialysis, attended at the hemodialysis center. The patients 'dietary and socioeconomic parameters were assessed using a questionnaire that was answered through individual interviews during the hemodialysis session and the assessment of existing comorbidities was defined after analysis of the patients' medical records. The results obtained showed that these were patients with a compromised socioeconomic profile, who had access to basic guidelines on food, due to the monitoring at the service, however, most of them had meals outside the home, which often made their choices impossible, as well as the limitation caused by the factor. Their nutritional status is strongly correlated with the existing pathology and the psychoemotional state.